Sistemas de Información como Herramienta de Inteligencia Analítica en las Empresas de Servicios Turísticos de México - Silva, José Luis Bravo; Aguas, Carlos Alberto García (European Scientific Journal, ESJ, 2019)
Information systems are a key element for the analysis of competitive information and the deployment of the intelligence function. This paper focuses on studying the existing relationship between the use of information systems and the process of analytical intelligence in tourism services companies in an important beach tourism area of Mexico. The type of study is descriptive, correlational, with a quantitative approach that includes the review of scientific literature, the critical analysis of data, the processing and systematization of these data, and the verification of the hypotheses proposed by the rho Spearman’s correlation coefficient. The results indicate that the process of analytical intelligence in this group of companies is influenced by the potential use of information systems, and there is a positive linear relationship between both variables (.693). Los sistemas de información son un elemento clave para el análisis de información competitiva y el despliegue de la función de inteligencia. Por esta razón, el propósito de este trabajo es estudiar la relación que existe entre el uso de sistemas de información y el proceso de inteligencia analítica en las empresas de servicios turísticos de una importante zona turística de México. El tipo de estudio es descriptivo, correlacional, y con un enfoque cuantitativo que comprende la revisión de literatura científica, el análisis crítico de datos, el procesamiento y sistematización de esos datos, y la comprobación de la hipótesis planteada mediante el coeficiente de correlación rho de Spearman. Los resultados indican que el proceso de inteligencia analítica en este grupo de empresas está influenciado por el potencial de uso de sistemas de información, existiendo una relación lineal positiva entre ambas variables (.693).